Intestinal Antibody Responses to 2 Novel Live Attenuated Type 2 Oral Poliovirus Vaccines in Healthy Adults in Belgium. (24th December 2020) - Brickley, Elizabeth B; Connor, Ruth I; Wieland-Alter, Wendy; Weiner, Joshua A; Ackerman, Margaret E; Arita, Minetaro; Gast, Chris; De Coster, Ilse; Van Damme, Pierre; Bandyopadhyay, Ananda S; Wright, Peter F
Abstract: In a blinded phase 1 trial (EudraCT 2017-0000908-21; NCT03430349) in Belgium, healthy adults (aged 18–50 years) previously immunized exclusively with inactivated poliovirus vaccine were administered a single dose of 1 of 2 novel type 2 oral poliovirus vaccines (nOPV2-c1: S2/cre5/S15domV/rec1/hifi3 (n = 15); nOPV2-c2: S2/S15domV/CpG40 (n = 15)) and isolated for 28 days in a purpose-built containment facility. Using stool samples collected near days 0, 14, 21, and 28, we evaluated intestinal neutralization and immunoglobulin A responses to the nOPV2s and found that nOPV2-c1 and nOPV2-c2 induced detectable poliovirus type 2–specific intestinal neutralizing responses in 40.0% and 46.7% of participants, respectively. Abstract : In a phase 1 trial, 2 novel type 2 oral poliovirus vaccine candidates induced detectable poliovirus type 2–specific intestinal neutralizing responses in 40.0% and 46.7% of participants, respectively, suggesting potential utility for reducing circulating vaccine-derived poliovirus transmission under outbreak scenarios.